Menstrual patterns and self-reported hirsutism as assessed via the modified Ferriman-Gallwey scale: A cross-sectional study. (May 2020) - Willis, Sydney K.; Mathew, Hannah M.; Wise, Lauren A.; Hatch, Elizabeth E.; Wesselink, Amelia K.; Rothman, Kenneth J.; Mahalingaiah, Shruthi
Abstract: Objective: Hirsutism, the presence of excess terminal hair in a male pattern, is a clinical marker of androgen excess in women. We used cross-sectional data from a North American preconception cohort study to evaluate the association between menstrual cycle characteristics and hirsutism. Study Design: Women aged 21–45 years were recruited to a North American cohort of pregnancy planners. On the baseline questionnaire, participants self-reported menstrual characteristics, which included menstrual regularity, cycle length, bleed length, and bleed heaviness. Participants provided a self-rating of hirsutism in nine distinct body areas using pictograms representing the modified Ferriman-Gallwey (mFG) score. Using their ratings, we calculated total mFG scores and defined hirsutism as mFG scores ≥8. We used log-binomial regression models to estimate prevalence ratios (PRs) for the association between menstrual characteristics and hirsutism assessed at baseline. Results: We included 5, 542 women in the analytic cohort. Mean mFG score was 4.7, with 21.7 % reporting mFG scores ≥8. Compared with women with regular menstrual cycles, irregular cycles were positively associated with mFG ≥8 (PR 1.73, 95 % CI 1.56–1.91). Bleed lengths of ≥7 days compared with <3 days also showed a positive association with mFG score ≥8 (PR 1.59, 95 % CI 1.16–2.19), as did heavy bleeds (PR 1.42, 95 % CI 1.21–1.67) compared with moderate bleeds. Findings remained consistent when restricted to women without a prior diagnosis of polycystic ovary syndrome. Conclusions: In a population-based cohort of North American women, menstrual irregularity, increased cycle and bleeds lengths, and heavier menstrual bleeds were associated with self-reported hirsutism.